Pentingnya E-Commerce Dan Sistem Informasi Dalam Pengambilan Keputusan Untuk Berwirausaha - Dekeng Setyo Budiarto; Ayu Putri Meylina; Rani Eka Diansari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The graduates of universities have an essential role in creating entrepreneurial opportunities, so their ability to face competition needs to be improved. Therefore, higher education must provide provisions both as professionals and entrepreneurs. This study aimed to examine the effect of using e-commerce and information systems on entrepreneurial decisions. In addition, this study also examines whether there are differences between students who have businesses and others in entrepreneurial decisions which never have been discussing before. The sampling method used is purposive sampling with specific criteria. This study uses primary data by distributing questionnaires to 234 accounting students in Yogyakarta. The results of hypothesis testing show that the use of e-commerce and information systems influences entrepreneurial decisions. In addition, there are differences in entrepreneurial decisions between students who have businesses and others.